CONTROL OF WEEDS IN POST-EMERGENCE HERBICIDES USED IN CULTURE OF SUGAR CANE - Silva, Paulo Vinicius da (2015)
The implantation of the mechanized harvesting system of sugarcane led to changes in the production system, in the production system was the modification of the weed flora, promoting the emergence of weed species that weren`t present in the conventional production system where the sugar cane was burnt. The present work had the objective of determining dose response curves of the herbicides amicarbazone, saflufenacil, mesotrione and sulfentrazone in post-emergence, over the weed species Merremia aegyptia; Ipomoea purpurea; Luffa aegyptiaca; Mucuna aterrima e Ricinus communis. The experiment was conducted in a greenhouse, with delineation entirely randomized, with four repetitions. The treatments constituted of the spraying of different doses of the herbicides amicarbazone, saflufenacil, mesotrione and sulfentrazone over the weed plants M. aegyptia; I. purpurea; L. aegyptiaca; M. aterrima e R. communis when the plants had two pairs of true leaves. . The method used was the dose response curves, being sprayed doses equivalent to 1,5; 1,0; 0,5; 0,25 and 0,0 times the commercial dose of each product (amicarbazone, saflufenacil, mesotrione, and sulfentrazone). The herbicides were sprayed individually over each weed species,. By 7, 14 and 21 days after the applications of the treatments (DAT), the symptoms of phytotoxicity were visually evaluated, and by 21 DAT, the dry mass of the shoots was determined. The herbicides saflufenacil and mesotrione weren`t effective in controlling Luffa aegyptiaca e Ricinus communis, respectively. The application of the herbicides sulfentrazone and amicarbazone resulted in control superior to 80% for all weed species times the commercial dose studied. Therefore, different levels of susceptibility of the weed plants to post-emergent herbicides were observed. The herbicides amicarbazone and sulfentrazone were the most effective.